To separate or to integrate? The normative effect of national culture on organisational ambidexterity of automotive OEMs in transition towards electric mobility. (18th December 2020) - Müller, Lucas A.; Stephan, Michael
The automotive industry is undergoing a disruptive change towards a new era of electric mobility. This transition is characterised by the critical management challenge of organising and balancing traditional businesses and new venture lines, a phenomenon described as organisational ambidexterity. We investigate how OEMs with different cultural backgrounds handle this challenge. Our suggestion is that national culture plays a crucial role in the firms' organisational implementation of explorative and exploitative work since cultural values affect managerial behaviour and the choice of organisational designs. Based on an in-depth longitudinal analysis of eleven car manufacturers from six nations, this work scrutinises the implementation of different ambidexterity forms and contextualises the results with Hofstede's work on cultural dimensions. Our findings indicate that structural separation of explorative and exploitative behaviour occurs in organisations rooted in long-term oriented, collectivistic and uncertainty avoiding cultures. Integrative forms of ambidexterity are prevalent in organisations rooted in short-term orientated, individualistic and uncertainty accepting cultures.